Optimizing localization accuracy in peroneal artery perforator sequential flap transplantation with digital subtraction angiography and high-frequency ultrasound - Yong-Pei Chen; Hai-Yan Zhong; Rui Yang; Ming-Li Zou; Qian Wang; Yong Chen; Min Wang; Si-Ming Yuan (Journal of Plastic Surgery and Hand Surgery)
The peroneal artery perforator flap is widely used to repair deep defects in the distal lower leg and ankle. However, the success of flap transplantation depends on the accurate location of the peroneal artery perforators, which can be a challenge due to potential vascular damage and anatomical variations. This study utilizes digital subtraction angiography and high-frequency ultrasound to clarify the anatomical features of the peroneal artery and its perforators and accurately locate these perforators, thereby improving preoperative design and clinical outcomes. Peroneal artery perforator sequential flaps were employed to repair the wounds and donor sites, with the second donor site sutured directly. A total of 36 peroneal artery perforators were identified in seven patients, with an average of 5.14 perforators per patient. The majority of these perforators (47.22%) were concentrated in the middle segment of the lower leg. All flaps underwent tension-free primary closure and survived successfully, presenting a smooth appearance, a fine texture, and a color similar to that of the surrounding skin. Only a linear scar was left in the secondary donor site, which did not affect the overall appearance of the limb. This technique can accurately localize peroneal artery perforators, optimize the design of peroneal artery perforator sequential flaps, and facilitate the success of the surgery and postoperative esthetic recovery.